Prevalence of diphtheria and antimicrobial-resistant wound infections among asylum seekers in Heidelberg, Germany, August–October 2024 - Bernadette Walter; Katharina Lück; Maja Adam; Bettina Winter; Patryk Krauze; Jörg Rau; Nina Knab; Anne Kühn; Andreas Welker; Elisabeth Aichinger; Stefan Brockmann (PLoS ONE, 2026)
Purpose In the second half of 2022 and 2023, an increase of diphtheria cases among asylum seekers was observed in Europe, with 120 cases reported in the state of Baden-Wuerttemberg, Germany. We aimed to determine prevalence of infection or colonization with toxigenic Corynebacterium among asylum seekers arriving between August and October 2024 in Heidelberg, Germany. In addition, we assessed antimicrobial-resistant wound infections and diphtheria immunity levels in this population. Methods We conducted a cross-sectional study with a random sample of 1073 newly arrived asylum seekers. Consenting participants received a throat and, if applicable, wound swabs. Demographic, clinical and migration-related information was collected to identify potential risk groups. Throat swabs were tested for toxigenic Corynebacterium species, while wound swabs were additionally tested for other antimicrobial-resistant pathogens with relevance to therapeutic management. IgG antibody levels against diphtheria toxoid were quantified in serum samples of a random sub-sample. Results Of the participants, 75% were male (n = 804), and ages ranged from 15 to 60 years (median = 27 years). The most common nationalities were Syrian (n = 281), Turkish (n = 189) and Afghan (n = 117). No toxigenic Corynebacterium was identified. Thirty-seven participants carried inflamed wounds, of whom 18 (49%) had wounds infected with methicillin-resistant Staphylococcus aureus (MRSA), corresponding to 1.7% (95% CI 1.0–2.6%) of the entire study population. Overall, 38.0% (95% CI 33.3–44.8%) showed non-protective diphtheria antibody titers, while acceptance of the on-site diphtheria vaccination was high at 93% (n = 998). Conclusion While no toxigenic Corynebacterium was detected, low immunity levels and antimicrobial resistance findings underline the importance of early diagnosis, treatment and vaccination options in displaced populations.